UTILIZATION OF FRESNEL LENS AS SOLAR THERMAL COLLECTOR USING STIRLING ENGINE - Zikri, Ahmad (KINETIKA, 2017)
This solar energy stirling engine is one of the alternatives to be used as a power plant. This solar energy will beconcentrated and stored in the battery / battery with a heat source that is focused on the stirling engine with fresnel lens. Due to the non-continuous solar energy in order to generate electricity continuously, the thermal storage fluid is used and completed by isolator materials. This Thermal storage fluid can store heat for a long enough time so that the stirling machine can run when the sun is in an unstable state of irradiation. Fluid used in this research are paraffin liquid, lubricant oil and sesame oil. The ability of the thermal storage fluid to store heat will affect the power generated on the stirling engine. From these conditions, the researchers utilizing solar energy using a fresnel lens-based stirling engine using various isolator. During this test by determining the temperature of the thermal storage fluid can know the power generated from the stirling machine. The use of insulators with thermal conductivity values (k) of each test material were glasswool, styrofoam, polyurethane foam, and aluminum foil, is consecutively 0.038 W/moC, 0.033 W/moC, 11.6 W/moC, 0.062 W/moC. The observation results show that temperature drop from 200oC to 160oC using glasswool can hold longer for 8.2 minutes and styrofoam and polyurethane foam can withstand temperature dropping for 7 minutes. The avarages power generated using an insulator is 8 Watt